Cyanobacteria drive community composition and functionality in rock–soil interface communities. Issue 4 (3rd February 2015) - Valverde, Angel; Makhalanyane, Thulani P.; Seely, Mary; Cowan, Don A.
Abstract Most ecological research on hypoliths, significant primary producers in hyperarid deserts, has focused on the diversity of individual groups of microbes (i.e. bacteria). However, microbial communities are inherently complex, and the interactions between cyanobacteria, heterotrophic bacteria, protista and metazoa are likely to be very important for ecosystem functioning. Cyanobacterial and heterotrophic bacterial communities were analysed by pyrosequencing, while metazoan and protistan communities were assessed by T‐RFLP analysis. Microbial functionality was estimated using carbon substrate utilization. Cyanobacterial community composition was significant in shaping community structure and function in hypoliths. Ecological network analysis showed that most significant co‐occurrences were positive, representing potential synergistic interactions. There were several highly interconnected associations (modules), and specific cyanobacteria were important in driving the modular structure of hypolithic networks. Together, our results suggest that hypolithic cyanobacteria have strong effects on higher trophic levels and ecosystem functioning.